Occupation and Resilience: An Interdisciplinary Critical Interpretive Synthesis - Van Veenendaal, Julie Anne (Division of Occupational Therapy, 2025)
This research presents an interdisciplinary critical interpretive synthesis examining the constructs of occupation and resilience and how they are related. The construct of resilience, which is concerned with how people respond to adversity, has the potential to guide the development of more socially transformative praxis in both occupational therapy and occupational science. As theory and theorisation are the foundation of praxis, for resilience to be useful in the development of socially transformative praxis the theoretical relationship between resilience and occupation needs to be clarified. Aim: The aim of this research was to critically explore and synthesise theoretical relationships between the construct of occupation and socio-ecological understandings of resilience. Methodology: Given that resilience has been studied across many disciplines, and, that the study of occupation requires interdisciplinarity, this research was positioned within an interdisciplinary paradigm. The interpretive review methodology of critical interpretive synthesis was chosen as it is consistent with an interdisciplinary paradigm, adopts a critically reflexive stance, and can be used for the examination, synthesis, and generation of theory. Occupation and resilience were first examined as separate constructs before theory on the relationship between occupation and resilience was developed. Through a hermeneutic and iterative process, a total of 131 papers were included in the review. Sixty-three of these papers were on occupation and 68 on resilience. Patterns of meaning including key concepts, relationships between concepts and critiques of current theory were analysed through a process of thematic analysis, data abstraction and memo writing. Insights from this process and interviews with subject matter experts formed the basis of theorisation about the relationship between occupation and resilience. Findings: Occupation and resilience are best understood as overlapping constructs that describe everyday processes. Occupation describes what people do as the point of intersection between people, space, and time. As a concept, occupation can either be used as a noun to refer to specific things people do, or as a verb to refer to process of being occupied. Resilience is an overarching concept that includes understandings of available capacity, divergent processes and what people consider to be positive outcomes. Moreover, resilience can be understood as a pattern of occupational engagement that unfolds over time. As occupation is the mechanism for resilience, understanding occupation is key to understanding resilience. Conclusion: Understanding the relationship between occupation and resilience creates unique opportunities for the development of socially transformative praxis, not only within occupational therapy and occupational science, but throughout resilience studies